2019
DOI: 10.1101/603647
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantitative proteomic alterations of human iPSC-based neuronal development indicate early onset of Rett syndrome

Abstract: Rett syndrome (RTT) is a progressive neurodevelopmental disease often caused by mutations in the X-linked gene encoding methyl-CpG binding protein 2 (MeCP2). The mechanisms by which impaired MeCP2 induces the pathological abnormalities in the brain are not understood. To understand the molecular mechanisms involved in disease, we used an RTT patient induced pluripotent stem cell (iPSC)-based model and applied an in-depth high-resolution quantitative mass spectrometry-based analysis during early stages of neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Further investigation using SILAC revealed that NPCs lacking MECP2 have increased expression of LIN28, which is known to repress differentiation into glial cells [130]. A recent study using iPSC neuron of Rett syndrome patients identified 4 subsets of proteins that were differentially expressed, across time points involved in filipodia assembly, synapses, axon guidance, and cytoskeleton and translation [131]. This showed distinct temporal deficits during neuronal development, highlighting the fluid pathology underlying Rett syndrome.…”
Section: Proteomic Analysis Of 2d Human Ipsc-derived Neuron Culturesmentioning
confidence: 99%
“…Further investigation using SILAC revealed that NPCs lacking MECP2 have increased expression of LIN28, which is known to repress differentiation into glial cells [130]. A recent study using iPSC neuron of Rett syndrome patients identified 4 subsets of proteins that were differentially expressed, across time points involved in filipodia assembly, synapses, axon guidance, and cytoskeleton and translation [131]. This showed distinct temporal deficits during neuronal development, highlighting the fluid pathology underlying Rett syndrome.…”
Section: Proteomic Analysis Of 2d Human Ipsc-derived Neuron Culturesmentioning
confidence: 99%